The Influence of Dynamic Capabilities, Innovation, and Technology Information on Competitive Advantage (Survey on Clothing MSMEs in Sukabumi City) - Rismayanti, Siti Syaaidah; Sunarya, Erry; Danial, R. Deni Muhammad (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The phenomenon of increasingly fierce business competition requires entrepreneurs to adapt quickly to survive and thrive in a constantly changing market. This competition does not only come from fellow local MSMEs, but also from industrial-scale products with larger production capacities and more competitive prices. This study aims to analyze the influence of dynamic capabilities, innovation, and information technology on the competitive advantage of clothing MSMEs in Sukabumi City. The main problems faced are low adaptation to market changes, lack of product innovation, and lack of optimal use of information technology. The methods used are quantitative with descriptive and associative approaches, as well as multiple linear regression analysis. Data was collected through a questionnaire to 104 MSME actors in clothing with saturated sampling techniques. The results of the study show that the three variables have a positive and significant effect on competitive advantage, both simultaneously and partially. This emphasizes the importance of adaptation, innovation, and the use of technology in increasing the competitiveness of MSMEs in the midst of dynamic market competition.